2022
DOI: 10.2166/wst.2022.051
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of microbial agents as corrosion and scale inhibitor for industrial cooling water applications

Abstract: In this study, 6 strains of microbial agents were investigated as environment-friendly scale and corrosion inhibitors for industrial cooling water applications. The static jar tests along with characterization methods were applied to evaluate the scale inhibition performance. Results showed that under a concentration of 240 mg/L, the Nitrobacteria, Denitrobacteria and Lactobacillus agents reached high CaCO3 scale inhibition efficiencies of 83, 82, and 86% respectively. Characterization methods indicated the de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…The results showed that CMP had good corrosion and scale inhibition effect, and the corrosion inhibition rate on Q235 carbon steel reached 99.69%. Hu et al 9,10 evaluated the corrosion inhibition behavior of Bacillus cereus (B. cereus) on Q235 carbon steel in simulated cooling water, whose anticorrosion efficiency was 73.88%. The results showed that the addition of B. cereus increased the charge transfer resistance of the metal and reduced the corrosion current density, allowing it to attach to the surface of Q235 carbon steel to form a tight biofilm.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that CMP had good corrosion and scale inhibition effect, and the corrosion inhibition rate on Q235 carbon steel reached 99.69%. Hu et al 9,10 evaluated the corrosion inhibition behavior of Bacillus cereus (B. cereus) on Q235 carbon steel in simulated cooling water, whose anticorrosion efficiency was 73.88%. The results showed that the addition of B. cereus increased the charge transfer resistance of the metal and reduced the corrosion current density, allowing it to attach to the surface of Q235 carbon steel to form a tight biofilm.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is necessary to dedicate the active B. cereus dry powder to industrial cooling water corrosion protection. In our previous study, B. cereus inoculum was found to possess a certain corrosion inhibition property (Hu et al, 2022b), nevertheless, detailed performances as well as some possible in uencing factors are still not explored. Under this premise, this paper investigated the corrosion behavior of Q235 CS in simulated cooling water under the presence of B. cereus inoculum.…”
Section: Introductionmentioning
confidence: 99%
“…Some strains of P. fluorescens are considered to be a high-yield protein factories, producing medicinal, food, and industrial proteins (Landry et al 2003 ; Kumar and Bhalla 2005 ; Sadeesh Kumar et al 2015 ; Morihara and Homma 2018 ; Wang et al 2022 ). P. fluorescens can be grown in bioreactors at high densities and tolerates various fermentation conditions (Schneider et al 2005 ; Hu et al 2022 ). The strong growth, heat stability, and high-level production of recombinant proteins make P. fluorescens an ideal candidate for industrial applications and cost-effective in protein recovery due to their extracellular secretions in culture medium (Landry et al 2003 ; Chew et al 2005 ; Fairbairn and Law 1986 ; Hu et al 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…P. fluorescens can be grown in bioreactors at high densities and tolerates various fermentation conditions (Schneider et al 2005 ; Hu et al 2022 ). The strong growth, heat stability, and high-level production of recombinant proteins make P. fluorescens an ideal candidate for industrial applications and cost-effective in protein recovery due to their extracellular secretions in culture medium (Landry et al 2003 ; Chew et al 2005 ; Fairbairn and Law 1986 ; Hu et al 2022 ). Another advantage is that P. fluorescens is a possible expression host for a diverse range of recombinant proteins (Chew et al 2005 ; Zhang et al 2018 ; Sindhu and Manonmani 2018 ; Park et al 2020 ; Fabia et al 2021 ).…”
Section: Introductionmentioning
confidence: 99%